Infantile tremor syndrome, often overlooked diagnosis in dermatology - Dimple Chopra; Shayna Aulakh; Archit Garg; Aashi Garg (Wolters Kluwer Medknow Publications, 2022)
Infantile tremor syndrome (ITS) is a clinical condition defined by a tetrad of pallor, development regression, pigmentary changes, and hypotonia which may be accompanied by tremors. The clinical spectrum of ITS may also vary. Not every patient may present with all the symptoms, some of them may show only very subtle features of ITS which may lead to underdiagnosis of this condition in daily clinical practice. We report a case of ITS where the patient had predominantly dermatological features such as hyperpigmentation over the dorsal aspect of hands, knees, feet, axilla, buttocks, brittle nails, thin sparse hairs but without characteristic tremors. This report, with brief review of literature, tends to sensitize dermatologists to keep ITS as a differential diagnosis while dealing with infantile hyperpigmentation and recognizing it in pretremor stage, especially in the exclusive breastfed population of Indian children, where ITS is still widely prevalent.